Individual in vivo Profiles of Microglia Polarization After Stroke, Represented by the Genes iNOS and Ym1 - Collmann, Franziska M.; Pijnenburg, Rory; Hamzei-Taj, Somayyeh; Minassian, Anuka; Folz-Donahue, Kat; Kukat, Christian; Aswendt, Markus; Hoehn, Mathias (Frontiers in Immunology, 2019)
Microglia are the brain-innate immune cells which actively surveil their environment and mediate multiple aspects of neuroinflammation, due to their ability to acquire diverse activation states and phenotypes. Simplified, M1-like microglia are defined as pro-inflammatory cells, while the alternative M2-like cells promote neuroprotection. The modulation of microglia polarization is an appealing neurotherapeutic strategy for stroke and other brain lesions, as well as neurodegenerative diseases. However, the activation profile and change of phenotype during experimental stroke is not well understood. With a combined magnetic resonance imaging (MRI) and optical imaging approach and genetic targeting of two key genes of the M1- and M2-like phenotypes, iNOS and Ym1, we were able to monitor in vivo the dynamic adaption of the microglia phenotype in response to experimental stroke.